Prawo do udziału w wyborach na szczebl lokalnym jako forma partycypacji politycznej imigrantów Polska na the innych krajów europejskich. - Trojanowska-Strzęboszewska, Monika (Political Preferences, 2013)
The article analyzes the problem of immigrants' participation in the elections on a local level as a display of political activity and the means of integration of the country and its migrants. Assuming the European-wide perspective it is noticeable that given countries differentiate in the level of enabling immigrants to participate in the political life. In Scandinavia and several north European countries there is the highest rate of immigrants' participation, on the other hand, in the countries that joined the EU in 2004 the rate is the lowest. In 20l0 immigrants without the EU citizenship were able to run for the local elections in l3 European countries and they had the voting right in l9 countries. In Poland only the EU citizens are allowed to participate in the elections. The research into the legal solutions enabling immigrants (especially those who are not from the EU) to acquire more voting rights proved to have interesting results. The research has shown that over a half of the people willing to parti- cipate in the parliamentary elections is for granting the voting rights to immigrants. According to the research among the electorates, the substantial percen- tage of the Platforma Obywatelska voters proved to be in favor of granting the voting rights to immigrants. Less support is displayed by the potential voters of SLD and Ruch Palikota. Furthermore, the majority of the PiS voters is against the immigrants' participation in the local elections. Finally, the results of the research show that voters perceive differently the problem of granting immi- grants the right to vote versus the right to stand for the elections. Although the first one is accepted by the majority of voters, the latter - not so much.